Automotive students' interest in e-commerce entrepreneurship: An exploration through a quantitative descriptive approach - Noor, Ridwan Adam M; Maulana, Indra; Gifari, M Maris Al; Samosir, Daniel Moses; Wiyono, Apri; Afiah, Syifa Kawakib Nurul (Universitas Negeri Padang, 2025)
This study explored the entrepreneurial interest in e-commerce among vocational high school students in the Motorcycle Engineering and Business program, with a focus on motorcycle spare parts sales. A descriptive quantitative approach was applied through a survey method involving 80 students. A questionnaire was employed to assess the level of entrepreneurial interest as well as the influencing factors, both intrinsic and extrinsic. The findings indicated that students’ interest in e-commerce entrepreneurship was at a moderate level, with intrinsic factors accounting for 56.98% and extrinsic factors for 43.02%. Motivation emerged as the most dominant intrinsic factor (14.51%), followed by perception, enjoyment, experience, and character. On the extrinsic side, the family environment exerted the strongest influence, followed by school and community. These results underscored the need to strengthen students’ digital entrepreneurial interest through contextual learning, hands-on activities, and supportive environments. The study also reinforced the relevance of Self-Determination Theory in explaining how intrinsic motivation influenced students’ entrepreneurial intentions in the digital economy.